Effect of molecular Stokes shift on polariton dynamics - Hulkko, E; Pikker, S; Tiainen, V; Tichauer, R H; Groenhof, G; Toppari, J J (The Journal of chemical physics, 2021)
When the enhanced electromagnetic field of a confined light mode interacts with photoactive molecules, the system can be driven into the regime of strong coupling, where new hybrid light-matter states, polaritons, are formed. Polaritons, manifested by the Rabi split in the dispersion, have shown potential for controlling the chemistry of the coupled molecules. Here, we show by angle-resolved steady-state experiments accompanied by multi-scale molecular dynamics simulations that the molecular Stokes shift plays a significant role in the relaxation of polaritons formed by organic molecules embedded in a polymer matrix within metallic Fabry-Pérot cavities. Our results suggest that in the case of Rhodamine 6G, a dye with a significant Stokes shift, excitation of the upper polariton leads to a rapid localization of the energy into the fluorescing state of one of the molecules, from where the energy scatters into the lower polariton (radiative pumping), which then emits. In contrast, for excitonic J-aggregates with a negligible Stokes shift, the fluorescing state does not provide an efficient relaxation gateway. Instead, the relaxation is mediated by exchanging energy quanta matching the energy gap between the dark states and lower polariton into vibrational modes (vibrationally assisted scattering). To understand better how the fluorescing state of a molecule that is not strongly coupled to the cavity can transfer its excitation energy to the lower polariton in the radiative pumping mechanism, we performed multi-scale molecular dynamics simulations. The results of these simulations suggest that non-adiabatic couplings between uncoupled molecules and the polaritons are the driving force for this energy transfer process.